PA Residues in the 2009 H1N1 Pandemic Influenza Virus Enhance Avian Influenza Virus Polymerase Activity in Mammalian Cells - Bussey, Kendra A. (American Society for Microbiology, 2011)

(untitled)
The 2009 pandemic influenza virus (pH1N1) is a swine-origin reassortant containing human, avian, and swine influenza genes. We have previously shown that the polymerase complex of the pH1N1 strain A/California/04/2009 (Cal) is highly active in mammalian 293T cells, despite the avian origin of both its PA and PB2. In this study, we analyzed the polymerase residues that are responsible for high pH1N1 polymerase activity in the mammalian host. Characterization of polymerase complexes containing various combinations of Cal and avian influenza virus A/chicken/Nanchang/3-120/01 (H3N2) (Nan) by reporter gene assay indicates that Cal PA, but not PB2, is a major contributing factor to high Cal polymerase activity in 293T cells. In particular, Cal PA significantly activates the otherwise inactive Nan polymerase at 37 and 39°C but not at the lower temperature of 34°C. Further analysis using site-directed mutagenesis showed that the Cal PA residues 85I, 186S, and 336M contribute to enhanced activity of the Cal polymerase. Recombinant A/WSN/33 (H1N1) (WSN) viruses containing Nan NP and polymerase (PA, PB1, PB2) genes with individual mutations in PA at residues 85, 186, and 336 produced higher levels of viral protein than the virus containing wild-type (WT) Nan PA. Interestingly, compared to the WT, the virus containing the 85I mutation grew faster in human A549 cells and the 336M mutation most significantly enhanced pathogenicity in a mouse model, among the three PA mutations tested. Our results suggest that multiple mutations in PA, which were rarely present in previous influenza isolates, are involved in mammalian adaptation and pathogenicity of the 2009 pH1N1.